Research on the Radiation Effects and Compact Model of SiGe HBT - Sun, Yabin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book primarily focuses on the radiation effects and compact model of silicon-germanium (SiGe) heterojunction bipolar transistors (HBTs). It introduces the small-signal equivalent circuit of SiGe HBTs including the distributed effects, and proposes a novel direct analytical extraction technique based on non-linear rational function fitting. It also presents the total dose effects irradiated by gamma rays and heavy ions, as well as the single-event transient induced by pulse laser microbeams. It offers readers essential information on the irradiation effects technique and the SiGe HBTs model using that technique.
Introduction -- Ionization damage in SiGe HBT -- Displacement damage with swift heavy ions in SiGe HBT -- Single-event transient induced by pulse laser microbeam in SiGe HBT -- Small-signal equivalent circuit of SiGe HBT based on the distributed effects -- Parameter extraction of SiGe HBT models -- Conclusion.
Keywords: Electronics; Semiconductors; Optical materials; Electronic circuits; Condensed matter; Electronics and Microelectronics, Instrumentation; Semiconductors; Optical Materials; Electronic Circuits and Systems; Condensed Matter Physics